Encyclopedia of the literature of empire - Snodgrass, Mary Ellen (Gale virtual reference library, 2009)
Surveys the world's greatest literature about empires and imperialism, written by citizens of these empires and the colonized people who lived under their rule. Examine authors, classic works, themes, and concepts, all related to particular empires in history or the general topics of imperialism and colonialism.